Knight of cups [videorecording (DVD)] - Malick, Terrence, 1943-; Bale, Christian, 1974-; Blanchett, Cate, 1969-; Portman, Natalie, 1981-; Banderas, Antonio (Broad Green Pictures, 2015)
The story follows writer Rick on an odyssey through the playgrounds of Los Angeles and Las Vegas as he undertakes a search for love and self. Even as he moves through a desire-laden landscape of mansions, resorts, beaches and clubs, Rick grapples with complicated relationships with his brother and father. His quest to break the spell of his disenchantment takes him on a series of adventures with six alluring women.